I have a feeling you wrote the question wrong
Isnt is supposed to be
2x^2 + 11x -51 = 0?????
(2x+17)(x-3)=0
2x+17=0: 2x=-17: x=-17/2
x-3=0: x=3
x=-17/2, x=3
if the question was written correctly, then yes you have to use the quadratic formula
2007-01-29 10:39:37
·
answer #1
·
answered by Bill F 6
·
0⤊
0⤋
No. You pretty much always want it to equal 0. You can simply use the quadratic equation to figure out the answer.
x = (-11 (+ or -) sqrt(11^2 - 4 * 2 * 51)) / (2 * 2)
You will get two answers, since there is an x^2 in the original equation.
P.S. Do not factor out an X!
2007-01-29 10:25:39
·
answer #2
·
answered by Bob 2
·
1⤊
0⤋
First, distribute the unfavorable signes in front of the 2d & third instruments. (x^2-11x+4) + (2x^2-2x+6) + (-x^2-6x+5) Now eliminate the parenthesis and combine like variables (ie. in basic terms upload x^2's together and in basic terms upload x's together.) 2x^2 -19x +15 this is your anser.
2016-12-16 16:30:19
·
answer #3
·
answered by hirschfeld 4
·
0⤊
0⤋
use the quadratic formula to solve it leaving the equation in the original way
try this link to understand it is really easy and with it you can resolve al of your problems
http://www.purplemath.com/modules/quadform.htm
your problem looks like this
x = (-11 (+ -) sqrt (11^2 - 4 * 2 * 51)) / (2 * 2)
2007-01-29 10:24:01
·
answer #4
·
answered by ? 5
·
1⤊
0⤋
You need to use the quadratic formula:
x=-b±√b^2-4ac/2a
a=2,b=11,c=51
x=(-11±√(11)^2-4(2*51))/2(2)
x=(-11±√121-4(102))/4
x=(-11±√121-408)/4
x=(-11±√-287)/4
There is no real solution because you cannot square out a negative number unless you use imaginary numbers. I hope this helps!
2007-01-29 10:34:58
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
ok u r right about the first part but you subtract 51 from the equation so you have this so you then have
2x+11=-51
-11 -11
2x=-62
2xover 2= -62over 2
x=-31
2007-01-29 10:23:43
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋
you need two numbers that multiplied give you -102 and added give you 11.
The numbers are 17 and -6
so you have:
2x^2-6x+17x-51=0
Factor
2x(x-3)+17(x-3)=0
rearenge:
(2x+17)(x-3)=0
so x=-17/2 or x=3
2007-01-29 10:27:58
·
answer #7
·
answered by ENA 2
·
0⤊
0⤋
no, you when you subtract you subtract -51,
so is 2x^2+11x=-51.
and you have to start from here.
2007-01-29 10:27:13
·
answer #8
·
answered by Ling T 3
·
0⤊
0⤋
im not sure but i got 2x^2+11x=-51
2007-01-29 10:22:54
·
answer #9
·
answered by ~Zaiyonna's Mommy~ 3
·
0⤊
1⤋
That wouldn't do you much good.
Use the quadratic formula
2007-01-29 10:23:40
·
answer #10
·
answered by alwaysmoose 7
·
0⤊
0⤋